Hubungan Antara Tekanan Darah Sistolik Dengan Kadar Ldl (Low Density Lipoprotein) Padapasien Diabetes Melitus Tipe 2 Di Klinik Arafah, Lampung Tengah - Avi Hurriyatus Sholihah; Firhat Esfandiari; Sandhy Arya Pratama; Resti Arania (MAHESA : Malahayati Health Student Journal, 2021)
ABSTRACT: RELATIONSHIP BETWEEN SYSTOLIC BLOOD PRESSURE WITH LDL (LOW DENSITY LIPOPROTEIN) IN DIABETES MELLITUS TYPE 2 PATIENTS IN ARAFAH CLINIC, CENTRAL LAMPUNG  Background: According to the 2017 World Health Organization (WHO), type 2 diabetes mellitus and hypertension ( HT) is a common disease among older adults aged> 60 years in developing and developed countries. One of the factors of hypertension is high levels of fat at high levels of fat, levels of LDL (Low Density Lipoprotein) are very influential and can lead to atherosclerosis that triggers hypertension. Of the 46 subjects, the frequency distribution of the sexes was male as many as 16 people (34.8%), female 30 people (65.2%). According to age <30 years as many as 2 people (4.3%), 30-50 years as many as 8 people (17.4%),> 50 years as many as 36 (78.3%). According to normal systolic blood pressure <140 mmHg as many as 34 people (73.9%), Height> 140 mmHg as many as 12 people (26.1%). And according to normal LDL levels <100 mg / dl as many as 8 people (17.4%), height> 100 mmHg as many as 38 people (2.6%). Objectives: to determine the relationship between systolic blood pressure and LDL (Low Density Lipoprotein) levels in patients with type 2 diabetes mellitus at the Arafah clinic, Central Lampung, 2020. Methods: This study used a cross sectional approach, namely by collecting data at the same time as one time. The data will be processed and analyzed with the help of a computer using the SPSS for Windows version 20.0 program. Results: Based on the Chi-Square analysis, it was found that there was no relationship with the value of p = 0.336 (p> 0.05). Conclusion: There is no relationship between systolic blood pressure and LDL (Low Density Lipoprotein) levels in patients with type 2 diabetes mellitus.                                                                                                 Keywords: Systolic blood pressure, LDL Levels, Diabetes Mellitus type 2.        INTISARI: HUBUNGAN ANTARA TEKANAN DARAH SISTOLIK DENGAN KADAR LDL (LOW DENSITY LIPOPROTEIN) PADA PASIEN DIABETES MELITUS TIPE 2 DI KLINIK ARAFAH, LAMPUNG TENGAH.Latar Belakang: Menurut World Health Organization tahun 2017 (WHO), diabetes melitus tipe 2 dan hipertensi (HT) adalah penyakit yang umum dikalangan orang dewasa tua berusia > 60 tahun di negara berkembang dan negara maju. Salah satu faktor hipertensi ialah tingginya kadar lemak pada tingginya kadar lemak, kadar LDL (Low Density Lipoprotein) sangat berpengaruh dan dapat mengakibatkan sebuah aterosklerosis pemacu hipertensi. Dari 46 subjek didapatkan distribusi frekuensi jenis kelaminnya laki laki sebanyak 16 orang (34,8%), perempuan 30 orang (65,2%). Menurut umurnya <30 tahun sebanyak 2 orang (4,3%), 30 – 50 tahun sebanyak 8 orang (17,4%), >50 tahun sebanyak 36 (78,3%). Menurut Tekanan darah sistoliknya Normal <140 mmHg sebanyak 34 orang (73,9%), Tinggi >140 mmHg sebanyak 12 orang (26,1%). Dan Menurut Kadar LDLnya normal <100 mg/dl sebanyak 8 orang (17,4%), tinggi >100 mmHg sebanyak 38 orang (2,6%).Tujuan: untuk mengetahui hubunganan antara tekanan darah sistolik dengan kadar LDL (Low Density Lipoprotein) pada pasien diabetes melitus tipe 2 di klinik Arafah, Lampung tengah tahun 2020.Metode: Penelitian ini menggunakan pendekatan cross sectional, yaitu dengan cara pengumpulan data sekaligus pada satu waktu. Data akan diolah dan dianalisa dengan bantuan komputer dengan menggunakan program SPSS for Windows versi 20,0.Hasil: Berdasarkan analisa Chi-Square didapatkan tidak adanya hubungan dengan nilai nilai p =0,336 (p>0,05).Kesimpulan: Tidak terdapat hubungan antara tekanan darah sistolik dengan kadar LDL (Low Density Lipoprotein) pada pasien diabetes melitus tipe 2. Kata Kunci : Tekanan darah sistolik, Kadar LDL, Diabetes Melitus tipe 2.